Primary myelofibrosis and pregnancy outcomes after low molecular-weight heparin administration: A case report and literature review. Issue 46 (November 2017) - Bohîlţea, Roxana Elena; Cîrstoiu, Monica Mihaela; Ionescu, Crîngu Antoniu; Niculescu-Mizil, Emilia; Vlădăreanu, Ana Maria; Voican, Irina; Dimitriu, Mihai; Turcan, Natalia
Abstract: Rationale: Primary myelofibrosis is encountered with the myeloproliferative diseases and is the least prevalent among women of childbearing age. The prognosis is guided by pancytopenia, leukemic transformation and thrombosis which are the dominant complications. Patient concerns: Data regarding protocol management during pregnancy in the context of myelofibrosis are insufficient. Fewer than ten cases have been described until now and half of this cases have resulted in fetal death due to placental infarction during the second and third trimesters. Diagnoses: We present the case of a 34-year-old pregnant woman diagnosed with Jak 2- negative primary myelofibrosis. Personal history did not include miscarriage or stillbirth. Interventions: The patient was previously treated with anagrelide hydrochloride, which was interrupted at 6 weeks of gestation when the pregnancy was confirmed. It was replaced with Interferon-a 3 MU/day. Because of severe thrombocytosis, administration of aspirin 150 mg/day was recommended. Outcomes: The pregnancy was uneventful. The patient was hospitalized at 33 weeks of gestation because of moderate vaginal bleeding and high risk of preterm birth. After a specialized hematological investigation, the treatment with aspirin was replaced with low-molecular-weight heparin 0.6 ml per day. This combined treatment assisted in the natural tendency to lower platelet counts during pregnancy and resulted in stabilization of the hematological status. At 38 weeks of gestation the patient delivered a healthy baby boy via cesarean. He weight 2850 grams and his Apgar score was 9. Anticoagulant and interferon treatments were continued post-partum under hematologist surveillance. Lessons: This case was rare and complex. Because it was related to pregnancy it required continuos collaboration and supervision between obstetrician and hematologist.